2020
DOI: 10.3390/jcm9113568
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Trends in Potential Drug Interactions with Direct-Acting Oral Anticoagulants in Patients with Atrial Fibrillation: An Australian-Wide Study

Abstract: Background: Co-prescribing medications that can interact with direct-acting oral anticoagulants (DOACs) may decrease their safety and efficacy. The aim of this study was to examine the co-prescribing of such medications with DOACs using the Australian national general practice dataset, MedicineInsight, over a five-year period. Methods: We performed five sequential cross-sectional analyses in patients with atrial fibrillation (AF) and a recorded DOAC prescription. Patients were defined as having a drug interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
(27 reference statements)
1
14
0
Order By: Relevance
“…The most frequently interacting drugs in these 3 large studies were phenytoin, nonsteroidal antiinflammatory drugs (NSAIDs), diltiazem, amiodarone, rifampicin, and verapamil. [31][32][33] Our research found carbamazepine, phenytoin, rifampicin, and enzalutamide in the severe interaction group (class X), and the most frequent class D interacting agents were diclofenac, dexketoprofen, naproxen, acetylsalicylic acid, clopidogrel, and propafenone in the moderate interaction group. In our study, the clinical relevant interaction was level was 20%, lower than the previous cohort study reported by Bezahbe et al 33 Different drug interaction assessment methods could explain this.…”
Section: Discussionmentioning
confidence: 68%
“…The most frequently interacting drugs in these 3 large studies were phenytoin, nonsteroidal antiinflammatory drugs (NSAIDs), diltiazem, amiodarone, rifampicin, and verapamil. [31][32][33] Our research found carbamazepine, phenytoin, rifampicin, and enzalutamide in the severe interaction group (class X), and the most frequent class D interacting agents were diclofenac, dexketoprofen, naproxen, acetylsalicylic acid, clopidogrel, and propafenone in the moderate interaction group. In our study, the clinical relevant interaction was level was 20%, lower than the previous cohort study reported by Bezahbe et al 33 Different drug interaction assessment methods could explain this.…”
Section: Discussionmentioning
confidence: 68%
“…Details about this dataset can be found elsewhere. [17][18][19][20][21][22][23][24] Patients newly diagnosed with AF from 1 January 2007 to 31 December 2008 ('screening period') and aged 18 years or more were included in this study. Baseline CHA 2 DS 2 -VA scores were calculated by assessing documented comorbidities until 31 December 2008.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 400 practice sites contributed data for this study. Details about this dataset can be found elsewhere 17‐24 . Patients newly diagnosed with AF from 1 January 2007 to 31 December 2008 (‘screening period’) and aged 18 years or more were included in this study.…”
Section: Methodsmentioning
confidence: 99%
“…15 Details about this dataset can be found elsewhere. [15][16][17][18] Patients newly diagnosed with AF in Australian general practices between 1 January 2009 and 25 April 2019 were included in this study. Patients were defined as having a new AF diagnosis based on their first-ever recorded diagnosis date within the study period.…”
Section: Methodsmentioning
confidence: 99%
“…It includes patient demographics, diagnoses, prescribed medications, pathology test results, observations and reasons for encounters 15 . Details about this dataset can be found elsewhere 15‐18 …”
Section: Methodsmentioning
confidence: 99%